Helping Them To Be Good Teachers: How Community Service Equips Pre-Service Teachers to Teach English - Yoedo, Yuli Christiana; Puspitasari, Dani (Universitas Pendidikan Mandalika, 2023)
Investigating pre-service teachers’ beliefs gives tremendous advantages for their future career development. This study was conducted in the context of elementary education. It focused on investigating the pre-service teachers’ beliefs about teaching English and how the teacher’s reflections changed their initial beliefs. We examined nineteen sophomore students who participated in community service to teach English at a public elementary school. A qualitative design was applied and reflections were carried out. Data were gathered through in-depth interviews and direct classroom observations. The result generates that many preservice teachers hold their prior beliefs about teaching from their student experience. Teaching reflections facilitate these pre-service teachers to realize their gaps in teaching skills. The finding suggests that teacher training faculty need to add more practical courses to nurture teaching skills. The findings may be useful for a larger population where English was taught as a foreign language for pre-service teachers and elementary school students. This study concludes that real teaching experience develops pre-service teachers’ professionalism. It impresses upon them that teaching needs comprehensive knowledge and skills.